Effect of Er:YAG laser cavity preparation on the bond strength of 2-hydroxyethyl methacrylate-free and 2-hydroxyethyl methacrylate-rich self-etch adhesive systems: An in vitro study - Atul Kumar Bishnoi; Rohit Adyanthaya; Shakti Singh; Abbas S Kapasi; Kanu Jain (Wolters Kluwer Medknow Publications, 2019)
Background: Despite many advantages of lasers and reduction of the risk of surface bonding errors with newer self-etch systems, they have not been thoroughly researched. This study was done to evaluate the effect of Er:YAG laser cavity preparation on the microtensile bond strength of 2-hydroxyethyl methacrylate (HEMA)-rich and HEMA-free one-step self-etch adhesive systems. Materials and Methods: In this in vitro study, eighty freshly extracted human premolars were collected. Cavities were prepared in 40 teeth with carbide bur (Group 1) and in other 40 teeth with Er:YAG LASER (490 mJ and 15 Hz) (Group 2). Subgroups of twenty teeth each were made according to the adhesive systems used. After placement of restoration, the mean values of the bond strength were calculated using universal testing machine. Data were then tabulated and analyzed using descriptive statistics (Significant at P < 0.05). Results: The overall microtensile bonding strength was higher when the cavities were prepared with bur compared to those with Er:YAG laser. Mean bond strengths of single-bottle self-etching seventh-generation dentin bonding agents to bur-prepared cavities were higher than those to laser-prepared cavities irrespective of the adhesive system (P = 0.01). No statistically significant difference was observed between HEMA-free and HEMA-rich self-etch adhesive systems. Conclusion: The effect of Er:YAG laser for cavity preparation did not show improved performance when evaluated using microtensile bond strength with seventh-generation bonding agents, Adper Easy One and G-Bond. More studies are required to assess the effect of lasers.